The impact of gut microbiota on mental health - Neska Aleksandra; Kedzierska Ewa; Gibula-Tarlowska Ewa (Current Issues in Pharmacy and Medical Sciences)
Microorganisms inhabit various areas of the human body, but by far the most numerous and diverse in species is the intestinal microbiota. This consists of an enormous number of microorganisms, the largest group of which are bacteria. Currently it is well known that microbiota affects the proper functioning of the brain, therefore, it has become the subject of interest in the field of mental diseases treatment. Numerous studies have shown both quantitative and qualitative disturbances in the composition of the intestinal microbiome in people suffering from depression. Psychobiotics are a category of probiotics that influence the gut microbiota and positively impact brain and nervous system function. The potential antidepressant role of psychobiotics is also indicated, however, presently, they do not have the status of drugs. It is well known that they induce various beneficial effects, such as reducing the level of cortisol and the activity of the hypothalamic-pituitary-adrenal (HPA) axis, as well as modulating the activity of the vagus nerve. Furthermore, the studies conducted so far allow to confirm the relationship between the composition and abundance of intestinal microflora and occurrence of various mental diseases, including: depression, schizophrenia, bipolar disorder, autism and attention deficit hyperactivity disorder (ADHD).